Implementing Merdeka Belajar–Kampus Merdeka in Arabic Language Education: A Qualitative Case Study on Curriculum Transformation and Graduate Readiness - Rosidah; Maksum, Ali; Tutiawati, Siti (Al-Qalam Institue, 2025)
This study explores the implementation of the Merdeka Belajar–Kampus Merdeka (MBKM) curriculum in the Arabic Language Education Program at Universitas Islam Negeri Sultan Maulana Hasanuddin Banten. The MBKM policy, introduced by the Ministry of Education, Culture, Research, and Technology of Indonesia, aims to strengthen graduate employability and institutional adaptability in the digital era. A qualitative case study design was employed. Participants were selected using purposive sampling targeting key academic stakeholders, followed by snowball sampling to identify additional informants. Data were collected through semi-structured interviews, non-participant observations, and document analysis, and analyzed using Miles and Huberman’s interactive model. Trustworthiness was ensured through triangulation and member checking. The findings reveal five core implementation strategies: leadership commitment, stakeholder engagement, MBKM-oriented curriculum redesign, external partnerships, and internal quality assurance. The process unfolded in three phases: planning, execution, and monitoring. The study demonstrates that coherent governance and collaborative networks are critical enablers of MBKM adoption. These findings provide practical insights for Islamic higher education institutions implementing reforms based on outcome-based and experiential learning.